2020
DOI: 10.1103/physrevlett.125.081601
|View full text |Cite|
|
Sign up to set email alerts
|

Flavor Constraints from Unitarity and Analyticity

Abstract: We use unitarity and analyticity of scattering amplitudes to constrain fermionic operators in the standard model effective field theory. For four-fermion operators at mass dimension 8, we scatter flavor superpositions in fixed standard model representations and find the Wilson coefficients to be constrained so that their contraction with any pair of pure density matrices is positive. These constraints imply that flavor-violating couplings are upper bounded by their flavor-conserving cousins. For instance, LEP … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
76
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(77 citation statements)
references
References 56 publications
1
76
0
Order By: Relevance
“…Such relations, often denoted as sum rules, can be classified in terms of the energy expansion of the amplitudes analogous to the EFT operator expansion. In previous works, the main focus has been at the level of dimension-8 operators for which the sum rules can be interpreted as positivity bounds on certain operator coefficients (or combinations of them) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. This remarkable finding suggests that the possible parameter space in an EFT is already constrained by the fundamental properties of quantum field theory, i.e.…”
Section: Jhep03(2021)149mentioning
confidence: 99%
See 3 more Smart Citations
“…Such relations, often denoted as sum rules, can be classified in terms of the energy expansion of the amplitudes analogous to the EFT operator expansion. In previous works, the main focus has been at the level of dimension-8 operators for which the sum rules can be interpreted as positivity bounds on certain operator coefficients (or combinations of them) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. This remarkable finding suggests that the possible parameter space in an EFT is already constrained by the fundamental properties of quantum field theory, i.e.…”
Section: Jhep03(2021)149mentioning
confidence: 99%
“…A recent study on the flavor constraints from dimension-8 four-fermion operators can be found in ref. [16]. Given that we are working in the massless limit with no EWSB, we will parameterize the Higgs doublet as H = φ + φ 0…”
Section: Sum Rules Of Dimension-6 Operatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, many dimension-8 operators are subject to positivity bounds arising from fundamental principles of quantum field theory including unitarity and analyticity, see [20][21][22][23][24][25][26][27][28][29] for some recent applications. The LEFT is a valid EFT in its own right, independent of whatever its UV completion may be.…”
Section: Introductionmentioning
confidence: 99%